Leverage, Scale, and Firm Age as Determinants of Corporate Financial Distress: A Cox Proportional Hazard Analysis of Cyclical Sector Firms on the Indonesia Stock Exchange - Marta, Ahmadi; Zakiah, Amiratu (Universitas Trunodjoyo Madura, 2026)
Financial distress prediction in emerging markets demands methodologies that address both the probability and the timing of corporate financial failure. This study applies the Cox Proportional Hazard (Cox PH) model to examine survival time until financial distress among 166 companies listed on the Indonesia Stock Exchange (BEI) across three cyclical sectors (Basic Materials, Non-Primary Consumer Goods, and Energy) over the 2016–2024 observation period. Financial distress is operationalised using a multidimensional definition requiring at least two of three conditions simultaneously: Interest Coverage Ratio below unity, negative Operating Cash Flow, and negative Retained Earnings. Kaplan-Meier estimates indicate a cumulative distress incidence of 54.2%, with overall survival declining to S(t=9) = 0.46 (95% CI: 0.39–0.54). The log-rank test finds no significant difference across sectors (chi-square = 1.76, p = 0.416). The Cox PH model achieves strong fit (LR chi-square = 89.18, p 0.001) and excellent discriminatory ability (C-index = 0.807). Three covariates are statistically significant: Debt-to-Asset Ratio (HR = 2.05, p 0.001), Firm Size (HR = 0.64, p 0.001), and Firm Age (HR = 0.94, p 0.001). All proportional hazard assumptions are confirmed through Grambsch-Therneau diagnostics. Findings are consistent with Trade-off Theory, Agency Theory, the too-big-to-fail hypothesis, and the Liability of Newness framework, and are robust across parametric alternatives. Time-invariant covariates at a single lag constitute the principal limitation. These results offer empirical grounding for leverage-based financial distress early warning in the Indonesian market context, though sector-level heterogeneity in the leverage–distress mechanism warrants consideration in practice.